A utilização de linguagem VRML na educação à distância em arte - Ralha, Jurema Luzia de Freitas Sampaio [UNESP] (2003)
The idea of this paper is to propose an art study possibility helped by the computer connected to the web, using communication technologies and virtual reality simulation, checking on VRML language as a tool for creation, by simulation, of environments in 3D virtual reality to study some particular art aspects such as the 3D perception and putting together the main results, obtained from many different researches on the usage of VRML and its educational application, aiming to achieve the dimension of this possibility. I intend, as the main objective of the research, to study the VRML language as a support tool to optimize the construction on the art knowlegment. This proposal has, as the idea of an application, the development of a bigger concept comprehension in art's studies and still the learning of arts, on distance learning, through the experiences in art appreciation and sensorial involvement using virtual reality by the VRML language to promote the simulation e reproduction of visual master pieces in virtual reality and so on. This proposal doesn't intend to be an idea on the replacement of teachers and tutors on teaching and learning of virtual arts, quite the opposite, the idea is to offer access to materials in a different way and to a bigger number of people, through the anytime / anywhere possibilities of learning that are available on the distance learning digital technologies by the using of computers connected to the web, called e-learning. Basically, the paper is divided in three parts. 1. To propose the art study couting n the computer, communication techonologies and virtual reality simulation, 2. To research the VRML language as a tool to create the environment in virtual reality to study the 3D representation, and. 3. To put together the results already otained in many researches about the usage of VRML language its educational applicability, to get tlhe dimension of this proposal.